2022
DOI: 10.3389/fnut.2022.899004
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Adjusted Dietary Inflammatory Index Is Associated With 5-Year All Cause and Cardiovascular Mortality Among Chronic Kidney Disease Patients

Abstract: BackgroundDiet management is a pivotal intervention for chronic kidney disease (CKD) patients. Dietary inflammation index (DII) is developed to evaluate the integral inflammatory potential of a diet pattern. However, research about the association between DII and mortality in CKD is limited.ObjectiveWe conducted a cohort study to investigate the relationship between energy-adjusted DII (E-DII) and the 5-year all-cause and cardiovascular mortality in CKD population.Materials and MethodsCKD participants with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…It has also been suggested that treatments using an anti-inflammatory diet might lower rates to get hyperparathyroidism in patients with CKD ( 24 ). Moreover, Ying Huang et al found that the association of elevated energy-adjusted dietary inflammatory index (E-DII) with increased risk of 5-year all-cause and cardiovascular mortality in individuals with CKD was not modified by other factors, while subgroup analyses showed that individuals with worsening renal function were more vulnerable to the effects of E-DII ( 25 ). With the aging of populations worldwide, researchers are increasingly concentrating on middle-aged and older populations, including DII-related studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that treatments using an anti-inflammatory diet might lower rates to get hyperparathyroidism in patients with CKD ( 24 ). Moreover, Ying Huang et al found that the association of elevated energy-adjusted dietary inflammatory index (E-DII) with increased risk of 5-year all-cause and cardiovascular mortality in individuals with CKD was not modified by other factors, while subgroup analyses showed that individuals with worsening renal function were more vulnerable to the effects of E-DII ( 25 ). With the aging of populations worldwide, researchers are increasingly concentrating on middle-aged and older populations, including DII-related studies.…”
Section: Discussionmentioning
confidence: 99%
“…DII was calculated using the approach reported by Shivappa et al [ 13 , 27 ]. The food intake data for each patient were converted into nutrient data based on the China Food Composition Table, Standard Edition, Sixth Version.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, standard values and standard deviations from the global database were converted accordingly, with all units expressed per 1000 kilocalorie energy intake [ 15 , 28 , 29 ]. Referring to previous studies related to the E-DII, prior to the analysis, three quartiles of the E-DII were created based on continuous E-DII scores, which served as the classification criteria for the E-DII as a categorical variable [ 21 , 22 , 27 ]. Tertiles 1, 2, and 3 represented patients with the lowest, intermediate, and highest potential for dietary inflammation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Current medical conditions were also included in our study based on self-reported forms or relevant laboratory or imaging findings: diabetes mellitus (yes/no), hypertension (yes/no), congestive heart failure(yes/no), stroke(yes/no), osteoarthritis(yes/no), osteoporosis(yes/no), cancer(yes/no), chronic kidney disease(CKD)(yes/no), and chronic obstructive pulmonary disease(COPD)(yes/no). The diagnosis of CKD was based on the estimated glomerular filtration rate [eGFR] < 60 ml/min per 1.73 m2 or urine albumin-to creatinine ratio (ACR) ≥ 30 mg/g [ 29 , 30 ]. The diagnosis of osteoporosis was based on bone mineral density, which was evaluated by evaluated by dual-energy X-ray absorptiometry scans with Hologic QDR-4500 A fan-beam densitometers (Hologic, Inc., Bedford, Massachusetts).…”
Section: Methodsmentioning
confidence: 99%